Four new species of the genus Omaliopsis Jeannel, 1940 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) of China - Shavrin, Alexey V. (Zootaxa, 2023)
Four new closely related species of the genus Omaliopsis Jeannel, 1940 (Omaliinae) from China are described and illustrated: O. fraterna sp. n. (Sichuan, Yunnan), O. hlavaci sp. n. (Sichuan), O. obliquesignata sp. n. (Shaanxi), and O. smetanai sp. n. (Sichuan, Shaanxi, Yunnan). An updated key to all Asian species of the genus is provided.